If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6n + -3 = 27 Reorder the terms: -3 + 6n = 27 Solving -3 + 6n = 27 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 6n = 27 + 3 Combine like terms: -3 + 3 = 0 0 + 6n = 27 + 3 6n = 27 + 3 Combine like terms: 27 + 3 = 30 6n = 30 Divide each side by '6'. n = 5 Simplifying n = 5
| -5(5-k)= | | 6m-9=33 | | 5y-2+y+40=8y+50-6y | | 3m-8=6+m | | 10x-11x=-9 | | 3b+7= | | 2(x-8)+4=-12 | | -2x^2+4x+15=0 | | -2x^2+4x+15=0 | | 6(3+3x)-5=49 | | 10-4p=56 | | y^2x-y^2+4x=0 | | 7y-18=5y+4 | | r^2+2r=35 | | x^2-x-208=0 | | 16-17z-19=-18-16z | | x(8x+1)=3x^2-20x+20 | | 2a-16=4a | | 8=4*3c+5 | | 9-2(5x+4)=-3(2x-7)-10 | | 0.4+-0.6=1.3k+1.2 | | 2(x-4)-5x=2+2x+5 | | 2x+8=3x-7 | | 11x=8x+6 | | M-(-5)=19 | | -11=11(r-3) | | 5y+9(3y+2)=274 | | 5(10x-4)-3x-7=13x-20 | | 5x-10+3x+20=180 | | r+6+4=10 | | 18s-17-7s=16+8s | | 3x+2+x=5x+5 |